De-Soekarnoisasi Dalam Wacana Resmi Orde Baru: Kilas-Balik Praktek-Praktek Rekayasa Kebenaran dan Wacana Sejarah Oleh Rejim Orde Baru - Sudibyo, Agus (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 1998)
New Order regime under Soeharto carried various ways out in order to weaken its rivals position. One of them is symbolical way, by using its formal discourses to create illegitimate and unfavourable construction on its rivals. This symbolical one is also applied to Bung Karno, the first President of Indonesia. Instead of less effectively legal-formal mechanisms to erode Bung Karnos influences, they delegitimated Bung Karnos in symbolical contex. This article looks that delegitimation practices to Bung Karno, or De-Soekarno-ization, is not only conducted on the level of manifest, for example by swept away Soekarnos loyalists fivm bureaucracy and military, but also on the level of symbolical-latent by negating and denying Bung Karnos historical roles and contributions. It occured in textual education books and government medias and on the various debate in mass media when apparatuses of New Order regime discreditted Bung Karno